Gettering in polySi/SiO xpassivating contacts enables Si-based tandem solar cells with high thermal and contamination resilience - Assar, Alireza; Martinho, Filipe; Larsen, Jes; Saini, Nishant; Shearer, Denver; Moro, Marcos V; Stulen, Fredrik Arnesen; Grini, Sigbjørn; Engberg, Sara; Stamate, Eugen; Schou, Jørgen; Vines, Lasse; et al. (ACS applied materials & interfaces, 2022)
Multijunction solar cells in a tandem configuration could further lower the costs of electricity if crystalline Si (c-Si) is used as the bottom cell. However, for direct monolithic integration on c-Si, only a restricted number of top and bottom cell architectures are compatible, due to either epitaxy or high-temperature constraints, where the interface between subcells is subject to a trade-off between transmittance, electrical interconnection, and bottom cell degradation. Using polySi/SiOx passivating contacts for Si, this degradation can be largely circumvented by tuning the polySi/SiOx stacks to promote gettering of contaminants admitted into the Si bottom cell during the top cell synthesis. Applying this concept to the low-cost top cell chalcogenides Cu2ZnSnS4 (CZTS), CuGaSe2 (CGSe), and AgInGaSe2 (AIGSe), fabricated under harsh S or Se atmospheres above 550 °C, we show that increasing the heavily doped polySi layer thickness from 40 to up to 400 nm prevents a reduction in Si carrier lifetime by 1 order of magnitude, with final lifetimes above 500 μs uniformly across areas up to 20 cm2. In all cases, the increased resilience was correlated with a 99.9% reduction in contaminant concentration in the c-Si bulk, provided by the thick polySi layer, which acts as a buried gettering layer in the tandem structure without compromising the Si passivation quality. The Si resilience decreased as AIGSe > CGSe > CZTS, in accordance with the measured Cu contamination profiles and higher annealing temperatures. An efficiency of up to 7% was achieved for a CZTS/Si tandem, where the Si bottom cell is no longer the limiting factor.